2003
DOI: 10.1161/01.res.0000084382.64418.bc
|View full text |Cite
|
Sign up to set email alerts
|

Direct Actions of Urotensin II on the Heart

Abstract: Abstract-Urotensin II (UII) is a somatostatin-like peptide recently identified as a potent vasoconstrictor. In this study, we examined whether UII promotes cardiac remodeling through nonhemodynamic effects on the myocardium. In a rat model of heart failure after myocardial infarction (MI), increased UII peptide and UII receptor protein expression was observed in both infarct and noninfarct regions of the left ventricle compared with sham. Moreover, post-MI remodeling was associated with a significant 75% incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(95 citation statements)
references
References 34 publications
3
87
0
5
Order By: Relevance
“…Similar to AngII (Chen et al 2004) and ET-1 (Chen et al 2005), UII-induced myocyte hypertrophy may contribute to cardiac remodeling and deterioration of cardiac function. Tzanidis et al (2003) demonstrated the expression of both UII and UII-R within myocardial tissue, suggesting an important role for UII in cardiac pathophysiology. Zhou et al (2003) reported UII-dependent hypertrophy in isolated cardiomyocyte cultures.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Similar to AngII (Chen et al 2004) and ET-1 (Chen et al 2005), UII-induced myocyte hypertrophy may contribute to cardiac remodeling and deterioration of cardiac function. Tzanidis et al (2003) demonstrated the expression of both UII and UII-R within myocardial tissue, suggesting an important role for UII in cardiac pathophysiology. Zhou et al (2003) reported UII-dependent hypertrophy in isolated cardiomyocyte cultures.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, UII may be an important determinant of cardiac dysfunction via additional nonhemodynamic effects on the myocardium, similar to angiotensin II (AngII) and ET-1 (Li et al 2005). Specifically, Tzanidis et al (2003) reported that UII stimulates collagen synthesis in cardiac fibroblasts, suggesting that UII may be involved in myocardial fibrogenesis. UII and its receptor (UII-R) are upregulated in patients with end-stage heart failure (Ng et al 2002), ischemia (Pakala 2008), chronic hypoxia (MacLean et al 2000), or post-myocardial infarct rat myocardium (Tzanidis et al 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-thin sections obtained from the embedded blocks were examined using a TEM (H-7500; Hitachi, Tokyo, Japan). Masson staining for collagen and streptavidin-biotin-peroxidase complex (SABC) immunohistochemistry staining for type-I collagen and type-III collagen (rabbit antibodies from Santa Cruz Biotechnol- ogy, Santa Cruz, CA, USA) were undertaken after 4-μm thick sections were obtained from the paraffin-embedded cardiac samples using previously described methods [20] . Results were expressed as the mean percentage area of 10 random fields for each section.…”
Section: Measurement Of Cardiac Contractile Functionmentioning
confidence: 99%
“…However, Ames et al discovered in anesthetized primates that low dose (<30 pmol/kg) administration of UTII resulted in increased cardiac output while high dose UTII (>30 pmol/kg) resulted in cardiovascular collapse due to decreased stroke volume with little change in heart rate [2]. Finally, the UTII system has been implicated in adverse remodeling and left ventricular hypertrophy as shown by increased collagen mRNA and protein expression as well as increase leucine incorporation in cell culture [12,26].…”
Section: Introductionmentioning
confidence: 99%